Moral Rationality and the Formation of Ethical Action: A Study of Aristotle's Thought - Yeyen Andrizal (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This study examines Aristotle’s conception of moral rationality and its role in the formation of ethical action. The research is grounded in the premise that reason constitutes the defining characteristic of human beings and serves as the primary foundation for moral judgment and ethical behavior. Employing a qualitative library research approach, the study analyzes Aristotle’s Nicomachean Ethics alongside relevant scholarly literature on virtue ethics, practical wisdom, and moral philosophy. Data were collected through a systematic review of primary and secondary sources and analyzed using descriptive and analytical methods to explore the relationship between reason, virtue, and action within Aristotle’s ethical framework. The findings reveal that moral rationality functions as the guiding principle of ethical action by enabling individuals to distinguish right from wrong and to act in accordance with virtue. Practical wisdom (phronesis) plays a crucial role in translating rational deliberation into concrete moral decisions, while virtue formation develops through habituation and continuous practice. The study further demonstrates that ethical character emerges from the integration of reason, emotion, and desire under the guidance of rational judgment. Ultimately, Aristotle’s concept of eudaimonia illustrates that genuine human flourishing is achieved through virtuous activity directed by reason. These findings highlight the enduring relevance of Aristotle’s ethical thought for contemporary discussions on moral education, character development, and ethical decision-making. The study contributes to moral philosophy by clarifying the systematic relationship between moral rationality and the formation of ethical action.